International center for monitoring cloud computing providers (ICMCCP) for ensuring trusted clouds - Mohammed, Mohssen M. Z. E.; Pathan, Al-Sakib Khan (2014)
Cloud computing offers flexible and scalable IT (Information Technology) services for which many organizations are now interested in harnessing its benefit. In spite of the enthusiasm and great interest, Cloud computing has not yet earned full trust of the individual customers, banks, armed forces, governments, and companies who do sensitive computing tasks. While it is not the goal to persuade everyone to use the technology and some types of tasks are to be done with secrecy, for the general works done by the companies and customers, Cloud could be heavily used. However, it is very difficult to convince people that the Cloud Providers (CPs) would keep their data protected. To address this issue, what required is to employ some mechanism that can establish the trust of the users. With this motivation, in this paper, we present a novel concept for trust assurance in Cloud services with the proposal of implementing a Global Central Bank-like regulatory authority. Our initiative is termed International Center for Monitoring Cloud Computing Providers (ICMCCP). Various facets of ICMCCP model have been described alongside the policy making issues. Necessary backgrounds of Cloud are also presented.